Locus of control in active physical therapy treatment for non-specific chronic low back pain - Alexandre Apolinário de Souza Batista; Leandro Silva Rezende Diniz; Vinícius Cunha Oliveira; Claudia Venturini
AbstractIntroduction The health locus of control is defined as the perception of individuals in relation to whom they believe to be responsible for their health condition, including low back pain.Objective To identify whether individuals suffering from chronic low back pain in active physical therapy treatment believe they are responsible for their own condition.Material and methods Cross-sectional study involving 28 patients under active physical therapy treatment for non-specific chronic low back pain. Sociodemographic data and low back characteristics - including disability and pain severity - were collected. The Multidimensional Health Locus of Control (MHLC) scale was used to assess the health locus of control.Results Participants undergoing active low back pain treatment presented a mean (SD) of 26 points (11.40) in a 0-100 point scale for disability and 6.39 points (2.24) on a 0-10 scale for pain. In relation to the health locus of control, the means (SD) for internal, external and chance subscales were, respectively: 29.32 (3.98), 24.75 (3.58), and 13.71 (6.67). 82.1% of the participants presented higher rates for internal locus of control.Conclusion Patients undergoing active treatment for chronic low back pain believe they are responsible for their own condition. Further longitudinal studies may determine whether active treatments affect the beliefs of low back pain patients.